Las estrategias de evaluación que utilizan los docentes para el desarrollo de aprendizajes en los estudiantes del primer año de bachillerato general unificado del colegio fiscal mixto Hernán Gallardo Moscoso en la asignatura de química. Periodo 2012- 2013 - Gutierrez Valdivieso, Karla Alejandra (2013)
The evaluation of the educational framework is always an instrumental role therefore is to serve the educational goals and achievement of learning . His contribution is to encourage and facilitate decisions that enable the fulfillment of the objectives and institutional goals. Against this proposed conducting research entitled: Assessment strategies used by teachers to develop learning in Freshman High School College Attorney General Joint Unified “Gallardo Hernan Moscoso “in the subject of Chemistry. Period from 2012 to 2013. The overall objective of the research was: to analyze assessment strategies that are implemented in the subject of Chemistry and develop learning what students in the first year of high school. According to the investigation, it has been possible to demonstrate that the use of assessment strategies in the teaching-learning process of the course presents traditional chemical characteristics, so the students developed learning are characterized by short-lived. From this perspective, then the research work it was found that students develop learning that the first year of General Unified School was characterized by rote and repetitive due to the limited use of different evaluation techniques. In the present investigation methods such as analytic-synthetic, statistical, descriptive phase to meet the interpretive analysis of the empirical data, and the inductive -deductive method which enables to interpret the data was used. Finally we worked with a population composed of two teachers and thirty-six students of the Department of Natural Sciences College of above; surveys were applied to collect information.